2023
DOI: 10.3390/en16073162
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Bio-Oil Quality of Residual Biomass Pyrolysis by Chemical Activation: Effect of Alkalis and Acid Pre-Treatment

Abstract: In this study, we investigated the acid (HCl) and alkali (KOH) chemical activation of açaí seeds (Euterpe Oleraceae, Mart.) pre-treatment before pyrolysis at temperatures of 350–450 °C in order to assess how reactions proceed when affected by temperature. Chemical composition of bio-oil and aqueous phase were determined by GC-MS and FT-IR. The bio-char is characterized by XRD. For the activation with KOH, the XRD analysis identified the presence of Kalicinite (KHCO3), the dominant crystalline phase in bio-char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…These findings are consistent with the bio-oil yields reported by Serrão et al [30], who conducted a study on the pyrolysis of Açaí seeds in a natural setting, and with the yields reported by Castro et al [11], who investigated the pyrolysis of Açaí seeds in pilot, bench, and laboratory scales. The bio-char yields obtained in this study are also in agreement with similar data reported in the literature for the pyrolysis of Açaí seeds, whether in their natural state [17][18][19] or chemically activated [8,[20][21][22][23][24][25][26][27][28][29][30][31]. It is important to note that the observed increase in bio-oil yield with increasing temperature is attributed to the temperature range being within the range of maximum decomposition, where the original material is primarily decomposed into its initial products.…”
Section: Effect Of Process Temperaturesupporting
confidence: 90%
See 4 more Smart Citations
“…These findings are consistent with the bio-oil yields reported by Serrão et al [30], who conducted a study on the pyrolysis of Açaí seeds in a natural setting, and with the yields reported by Castro et al [11], who investigated the pyrolysis of Açaí seeds in pilot, bench, and laboratory scales. The bio-char yields obtained in this study are also in agreement with similar data reported in the literature for the pyrolysis of Açaí seeds, whether in their natural state [17][18][19] or chemically activated [8,[20][21][22][23][24][25][26][27][28][29][30][31]. It is important to note that the observed increase in bio-oil yield with increasing temperature is attributed to the temperature range being within the range of maximum decomposition, where the original material is primarily decomposed into its initial products.…”
Section: Effect Of Process Temperaturesupporting
confidence: 90%
“…The impregnation process was conducted at room temperature. The formed suspension was then transferred to a paper filter, washed with 120 mL of distilled water, and left to rest for 24 hours, following a previously described method [31]. Subsequently, it was dried at 100 °C ± 5 °C for 24 hours.…”
Section: Physical Pre-treatment Of Açaí Seeds (Euterpe Oleracea Mart)mentioning
confidence: 99%
See 3 more Smart Citations